Front Cover: Photolabile Ru Model Complexes with Chelating Diimine Ligands for Light‐Triggered Drug Release (Eur. J. Inorg. Chem. 13/2018). Issue 13 (9th March 2018) - Battistin, Federica; Balducci, Gabriele; Wei, Jianhua; Renfrew, Anna K.; Alessio, Enzo
Abstract : The Front Cover shows how a drug can be inactivated by coordination to an inert and inactive (and possibly non‐toxic) ruthenium complex and remains "chained" (or caged) until it is photo‐released upon illumination with light of appropriate wavelength. This is one of the core concepts of photoactivated chemotherapy (PACT), in which the metal fragment behaves as a photo‐protecting group. The other face of the "PACT medal" focuses on the photo‐generated metal fragment, which becomes cytotoxic upon opening up the coordination positions. The cover was designed by Federica Battistin. More information can be found in theFull Paper by A. K. Renfrew, E. Alessio et al. For more on the story behind the cover research, see theCover Profile .